2017
DOI: 10.1073/pnas.1621069114
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor inhibition normalizes blood glucose in severe insulin-resistant mice

Abstract: Inactivating mutations in the insulin receptor results in extreme insulin resistance. The resulting hyperglycemia is very difficult to treat, and patients are at risk for early morbidity and mortality from complications of diabetes. We used the insulin receptor antagonist S961 to induce severe insulin resistance, hyperglycemia, and ketonemia in mice. Using this model, we show that glucagon receptor (GCGR) inhibition with a monoclonal antibody normalized blood glucose and β-hydroxybutyrate levels. Insulin recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 52 publications
11
55
0
Order By: Relevance
“…Our observations in T1D rodent models have been replicated by others who have met these results with skepticism (7). The results presented in PNAS further refine these conclusions (2). Using REGN1193, a fully human Gcgr monoclonal antibody, Okamoto et al (8) (Regeneron) have reported effective glucose control in diabetic rodents and primates.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Our observations in T1D rodent models have been replicated by others who have met these results with skepticism (7). The results presented in PNAS further refine these conclusions (2). Using REGN1193, a fully human Gcgr monoclonal antibody, Okamoto et al (8) (Regeneron) have reported effective glucose control in diabetic rodents and primates.…”
supporting
confidence: 57%
“…Pharmacological approaches to blunt gcg action have gained some traction as a potential antidiabetic approach. In PNAS, Okamoto et al (1,2) present two papers evaluating gcg blockade on islet physiology. First, they examine the mechanisms of α-cell hyperplasia, a phenomenon that stands as a potential roadblock in the use of these glucagon receptor (Gcgr) antagonists (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration . In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges . Thus, patients with insulin receptor loss of function mutations, manifested as severe insulin resistance and diabetes, ie, Rabson‐Mendenhall syndrome and other related diseases, may benefit from anti‐glucagon receptor therapy.…”
Section: Discussionmentioning
confidence: 81%
“…This is a seminal observation that was later confirmed by several independent research groups (Gerich et al, 1976;Felig et al, 1978;Butler and Rizza, 1991;Kelley et al, 1994). Subsequent studies showed that somatostatin-induced inhibition of postprandial glucagon secretion ameliorates hyperglycemia in patients with T2D (Gerich et al, 1974;Dinneen et al, 1995;Shah et al, 2000), and more recently that blocking glucagon action decreases hyperglycemia in a variety of species, including rodents (Mu et al, 2011;Kim et al, 2012b;Okamoto et al, 2017), rabbits (Brand et al, 1996), dogs (Rivera et al, 2007), nonhuman primates (Xiong et al, 2012;Okamoto et al, 2015), and humans (Petersen and Sullivan, 2001;Kelly et al, 2015;van Dongen et al, 2015;Kazda et al, 2016;Kostic et al, 2018). The virtues and limitations of antagonizing glucagon signaling for the treatment of diabetes have recently been highlighted in several review articles (Unger and Cherrington, 2012;Farhy and McCall, 2015;Lee et al, 2016b;Müller et al, 2017), with the implication that excess glucagon action can serve a greater role in the pathology of T2D than impaired insulin action (Unger and Cherrington, 2012).…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 84%